(untitled) (El Hilo de la Fabula, 2021)
In this paper a chapter on the reception of the Canti by G. Leopardi in Spain in the first half of the 20th century will be analized, specifically, the translations into Catalan that were published in the journals and newspapers in the years between the I World War and the Spanish Civil War. The text will be focused on the detailed analysis of the translations made by J.Mª Garganta for «La Nova Revista», in order to see his reading of Leopardi.